2021
DOI: 10.1186/s13075-020-02408-4
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of disease-modifying anti-rheumatic drugs: pathways to and predictors of tocilizumab monotherapy

Abstract: Background There are numerous non-biologic and biologic disease-modifying anti-rheumatic drugs (bDMARDs) for rheumatoid arthritis (RA). Typical sequences of bDMARDs are not clear. Future treatment policies and trials should be informed by quantitative estimates of current treatment practice. Methods We used data from Corrona, a large real-world RA registry, to develop a method for quantifying sequential patterns in treatment with bDMARDs. As a proo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Therefore, we placed medications, tocilizumab, and Janus kinase (JAK) inhibitors, together into one subgroup as medications that could be used as monotherapy, which were named other bDMARDs, in our analysis. Tocilizumab 22,23 and the target synthetic DMARDs, 24 for example, small molecules of medication, could be used as monotherapy which has been well documented. A combination of T‐ or B‐cell modulating therapies was demonstrated with the effect of adjusting adaptive immunity against osteoporosis development and fracture incidence in RA patients 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we placed medications, tocilizumab, and Janus kinase (JAK) inhibitors, together into one subgroup as medications that could be used as monotherapy, which were named other bDMARDs, in our analysis. Tocilizumab 22,23 and the target synthetic DMARDs, 24 for example, small molecules of medication, could be used as monotherapy which has been well documented. A combination of T‐ or B‐cell modulating therapies was demonstrated with the effect of adjusting adaptive immunity against osteoporosis development and fracture incidence in RA patients 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Predicting risk of needing treatment step up to tocilizumab in patients who do not respond to initial therapy is another example of applications of AI in monitoring disease course in RA. A logistic regression model [ 141 ] showed that higher age and remission CDAI were the most important risk and protective factors for tocilizumab monotherapy, respectively (OR = 1.04 and 0.17, respectively) when excluding other treatments as variables. For any tocilizumab use (either monotherapy or in combination), the highest and lowest ORs belonged to the number of comorbidities (OR = 1.16) and remission CDAI (OR = 0.20) (excluding other treatments as factors).…”
Section: Artificial Intelligence In Ramentioning
confidence: 99%
“…Table 8 summarizes studies implementing ML and DL for monitoring disease course and predicting prognosis [ 79 , 137 , 138 , 140 , 141 , 146 , 147 , 149 , 157 166 ].…”
Section: Artificial Intelligence In Ramentioning
confidence: 99%
“…For example, a transition from a TNFi to a non-TNFi b/tsDMARD appears the same in a Sankey diagram regardless of previous treatments. A different set of studies have focused on pathways to a particular type of therapy, for example tocilizumab monotherapy (14) or therapies with baricitinib (15), but they do not summarize the entire treatment strategy across the disease course.…”
Section: Introductionmentioning
confidence: 99%